Calculation Model of Regional Economic Growth Efficiency by Intelligently Optimized Interunit Layout. (23rd August 2022) - Song, Xiufeng; Ke, Jingying; Shen, Huayan
Abstract : With the development of the economy, especially since the reform and opening up, the actual conditions that China's economic development faces have also changed, and the development goals have also been adjusted accordingly. However, since the reform and opening up, China's economy has still largely relied on the extended reproduction of the extension type. It basically develops along a high-input, low-efficiency path. The effectiveness of regional economic development has always been one of the most important debates in economics, and it has attracted great attention in different countries and regions around the world. So far, people have conducted a lot of theoretical and practical research on the effectiveness of regional development and put forward many practical countermeasures. However, it has achieved little in practice, and the original form of high growth and low efficiency has not been effectively reversed. In this paper, economic development is divided into two parts. The first part consists of the impact of changes in the quantity of factors of production on economic growth and the impact of the efficiency of economic growth on the entire economy. The second part consists of the annual average efficiency of economic growth. The average annual contribution of various production factors to economic growth and the economic growth efficiency of changes in the allocation of capital industries were 6.21%, 5.02%, 4.05%, 3.9%, and 3.3%, respectively in the past five years.